Pengembangan Desain Pembelajaran PAI Berbasis Karakter di MTs ZAIDUL ALI - Raudatul Jannah (Ta'limDiniyah: Jurnal Pendidikan Agama Islam (Journal of Islamic Education Studies), 2022)
Abstract : Religious education is required not only to provide a deep understanding of Religion, but also to contribute to society in shaping character. Many efforts have been made to fulfill this demand, but have not produced significant results. This study offers an analysis and development of the learning design of character-based Islamic Education. What can be used by the teacher as a guide in designing or designing Islamic Education learning. This article attempts to analyze and provide development to the design of learning Islamic Education. The results of this study can be seen from the steps or ways in designing the learning of character-based Islamic Education and how to evaluate it. So that it can be used by the teacher when doing learning design so that the learning done can integrate character values in the learning process. Keyword : Development, PAI learning design, Character